IMPLEMENTING CONSTRUCTIVISM APPROACH IN ONLINE WRITING COURSE: LEARNERS’ NEED ANALYSIS - Lidwina Sri Ardiasih; Emzir Emzir; Yumna Rasyid (English Review: Journal of English Education, 2018)
Learning a new language is inevitably working on activities in relation to the four language skills, namely reading, listening, speaking and writing. Reading and listening are categorized as receptive skills, while speaking and writing are productive skills. Differing from the other skills, in developing writing skills learners do not merely focus on the writing products, but more on its process in which they have to follow certain steps. It is the teacher’s responsibility to guide the students to develop excellence in writing. Universitas Terbuka (UT), as a higher education institution applying distance learning, has provided an online tutorial (tuton) to enhance students’ writing skills. In this study, the writer focuses on students’ skills in writing essays, particularly argumentative essays. Furthermore, constructivism is taken as tutor’s point of view to evaluate the materials as well as the learning process in the tuton of PBIS4313/Writing III Course. This research aimed at analyzing the students’ perceptions about the needs of Writing III Course, regarding both the materials and the learning process, particularly the implementation of the constructivism approach. The descriptive qualitative method was applied in this research. An online survey was carried out to gain some information on the perceptions of the students regarding the learning materials as well as the learning approach needed in this course. From the online survey, it showed that more than 50% students find difficulties in writing. However, they shared their opinions about the needs of the materials appropriate for Writing III Course as the basic information for futher development of the materials. Moreover, this research also resulted in some learning activities to be designed based on the constructivism approach.Key Words: constructivism approach, online tutorial, writing skills, argumentative essay